2017
DOI: 10.2147/cia.s141753
|View full text |Cite
|
Sign up to set email alerts
|

Strontium ranelate treatment in a postmenopausal woman with osteonecrosis of the jaw after long-term oral bisphosphonate administration: a case report

Abstract: Bisphosphonates (BPs) suppress bone resorption and increase bone strength, thus reducing the risk of fracture. Oral BPs are widely used for the prevention and treatment of osteoporosis and osteopenia. Here, we describe the case of a postmenopausal woman who took oral alendronate for >3 years for osteoporosis. The patient presented at the clinic with sharp jaw pain and swelling on the left mandible 4 months after extraction of the third molar. Clinical examinations identified an inflamed mucosal opening with pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
4
0
6
Order By: Relevance
“…Strontium ranelate has been used as an effective therapeutic treatment in battling osteoporosis in women (postmenopausal) and men . It has been shown that strontium ranelate is capable of improving intrinsic bone tissue quality of osteoporotic bone and reducing the risk of fractures associated with the disease in various animal models as well as in humans .…”
Section: Discussionmentioning
confidence: 99%
“…Strontium ranelate has been used as an effective therapeutic treatment in battling osteoporosis in women (postmenopausal) and men . It has been shown that strontium ranelate is capable of improving intrinsic bone tissue quality of osteoporotic bone and reducing the risk of fractures associated with the disease in various animal models as well as in humans .…”
Section: Discussionmentioning
confidence: 99%
“…Zmniejsza aktywność osteoklastów, powoduje wzrost syntezy kolagenu przez osteoblasty oraz zmniejsza rozpuszczalność kryształów hydroksyapatytu. Dowiedziono, że ranelinian strontu ogranicza ryzyko złamań kręgów u kobiet z osteopenią i osteoporozą po roku terapii o 49%, a w grupie z zaawansowaną osteoporozą po 3 latach zaobserwowano redukcję ryzyka złamań odcinka bliższego kości udowej o 36% [38,39].…”
Section: Profilaktyka I Leczenie Następstwunclassified
“…Além disso, em pacientes oncológicos frequentemente há associação destas drogas à quimioterápicos e corticosteroides, que aumentam o risco da MRONJ (RUGGIERO et al, 2014;ZHANG et al, 2016;OTTO et al, 2018). Já entre pacientes portadores de osteoporose ou outras condições benignas em que esses medicamentos são empregados, frequentemente se administram drogas com menor potência e cujas doses medicamentosas são menores, o que determina menor risco de ocorrência da MRONJ (KHAN et al, 2015;PAN et al, 2017;IVANOVSKI, 2018).…”
Section: Introductionunclassified